The Strategy of Touchpoints Agricultural Tourism Services Based on the Motivation of Tourists (Case Study: South Khorasan Saffron Farm) - Seyed Ali FAREGH; Narges Rezaee (گردشگری و اوقات فراغت)
Agricultural endeavors alone are insufficient to meet the requirements of rural communities. Consequently, comprehensive investigations have been undertaken to assess the economic viability of tourism farms. Nevertheless, a field that holds promise for further exploration is the mapping of tourists’ experiences within agricultural landscapes. The focus of this study is on mapping the journey of tourists in agricultural settings, with South Khorasan province serving as the research area due to its potential. The research methodology employed a standard questionnaire tool, "Motivational factors in tourists," with a reliability higher than 0.95 according to Cronbach's alpha method for all dimensions. In addition to questionnaires, semi-structured and in-depth interviews were also conducted with 30 domestic agricultural tourists who visited a saffron farm in Birjand in November 1402. Due to the limited statistical population, the sample is equal to the population. Therefore, the census was taken. The results of the questionnaire data were analyzed using SPSS 26 software and a descriptive statistical test method. As a result, we identified the most important motivations of tourists and their components. The interview data was also analyzed using a qualitative method based on foundational data theory and employing open, central, and selective coding, which led to the discovery of tourists' touchpoints in three main categories: before the trip, during the trip, and after the trip. This research presents a strategy for creating or developing services by integrating tourists' motivation with touchpoints based on tourist expectations, offering practical insights for the development of agricultural tourism. In the end, five key requirements for the design of touchpoints in agricultural tourism farm services are introduced, providing actionable recommendations for stakeholders in the field.